Economic Analysis of Broiler Chicken Farming Enterprises in TRB1 Region - Eröz, Ahmet Feyyaz; Arıkan, Mehmet Saltuk (Kastamonu Üniversitesi, 2025)
Aim to study: The purpose of this study is to conduct an economic analysis of broiler meat production in the provinces of Elazığ, Bingöl, Malatya, and Tunceli located in the TRB1 region. The aim was to calculate the technical parameters and production costs of broiler meat production in the TRB1 region. Material and methods: The dataset for the study consists of production data collected through surveys from 162 broiler broiler farms selected through sampling between December 2024 and April 2025. The farms were divided into small (25,000), medium (25,001-35,000), and large (35,001 and above) farms based on their capacities, and unit costs and profits were calculated. Results: The average mortality rate across farms was 7.50%; live weight was 2.590 kg; fattening period was 41.57 days; fattening period was 5.39 cows/year; and feed conversion ratio was 1.659 kg. Of the total production cost, 94.28% consisted of variable costs and 5.72% consisted of fixed costs. The maintenance cost per kilogram of live weight was 5.23 TL, and the profit was 5.76 TL. Conclusion: While large-scale farms stand out with their high production capacity and low mortality rate, medium-sized farms achieve the highest live weights but lag behind in feed efficiency. Small farms, on the other hand, experience high mortality rates. Consequently, it is believed that different production strategies and management models should be implemented in the TRB1 region depending on the farm size.
Keywords: Veterinary Sciences (Other); Veteriner Bilimleri (Diğer)